Hunger : the Biology and Politics of Starvation. - Butterly, John R.; Shepherd, Jack. (Hanover : Dartmouth College Press, 2010)
A timely and provocative look at the role political developments and the biology of nutrition play in world famine.
The silent emergency -- The framework of understanding -- The basics of nutrition -- The anatomy and physiology of nutrition -- Agriculture: the birth of civilization ... and famine -- Responses on the ground -- Responses: government and international -- Responses to malnutrition -- Why do some people starve? -- Why do some people die? -- The biological basis for political behavior -- The right to food -- Best practices -- Prescription for change.
Print version record.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Famines; Hunger; Malnutrition; Starvation; Politics, Practical; Human rights; Starvation; Hunger; Socioeconomic Factors; Politics; Human Rights; Environment; Malnutrition; Famines; Faim; Malnutrition; Inanition; Politique; Droits de l'homme (Droit international); starvation; politics; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Politics, Practical; Human rights; Famines; Hunger; Malnutrition; Starvation